2020
DOI: 10.1038/s41418-020-0555-7
|View full text |Cite
|
Sign up to set email alerts
|

FOXF2 deficiency accelerates the visceral metastasis of basal-like breast cancer by unrestrictedly increasing TGF-β and miR-182-5p

Abstract: The mesenchymal transcription factor forkhead box F2 (FOXF2) is a critical regulator of embryogenesis and tissue homeostasis. Our previous studies demonstrated that FOXF2 is ectopically expressed in basal-like breast cancer (BLBC) cells and that FOXF2 deficiency promotes the epithelial-mesenchymal transition and aggressiveness of BLBC cells. In this study, we found that FOXF2 controls transforming growth factor-beta (TGF-β)/SMAD signaling pathway activation through transrepression of TGF-β-coding genes in BLBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…FOXF2, as a transcriptional regulator, was also found to have a transcriptional repression effect on the miR-200b ∼ 200a ∼ 429 locus in lung cancer (Kundu et al, 2016). Lu et al (2020) also reported that FOXF2 can negatively regulate the transcription of TGF-β isoforms (TGFB1, TGFB2, and TGFB3) in basal-like breast cancer. Thus, FOXF2 may play a tumor suppressor role through transrepressing gene expression.…”
Section: Discussionmentioning
confidence: 86%
“…FOXF2, as a transcriptional regulator, was also found to have a transcriptional repression effect on the miR-200b ∼ 200a ∼ 429 locus in lung cancer (Kundu et al, 2016). Lu et al (2020) also reported that FOXF2 can negatively regulate the transcription of TGF-β isoforms (TGFB1, TGFB2, and TGFB3) in basal-like breast cancer. Thus, FOXF2 may play a tumor suppressor role through transrepressing gene expression.…”
Section: Discussionmentioning
confidence: 86%
“…In TGF β induced EMT, FOXF2 upregulation is essential for the transcriptional inhibition of E-cadherin, destruction of cell adhesion, and EMT-related cell migration. On the other hand, TGF β and FOXF2 form a negative feedback loop mediated by miR-182-5p and SMAD3 in BLBC ( Lu et al, 2020 ). Decreased FOXF2 expression promotes TGF β signaling, which conversely silences FOXF2 by upregulating miR-182-5p.…”
Section: Survey Methodologymentioning
confidence: 99%
“…Decreased FOXF2 expression promotes TGF β signaling, which conversely silences FOXF2 by upregulating miR-182-5p. FOXF2 deficiency facilitates the visceral metastasis of BLBC ( Lu et al, 2020 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…The underlying mechanism involves the reciprocal repression loop between FOXF2 and transforming growth factor-β (TGF-β) (Fig. 2 ) 39 . These groundbreaking studies provided theoretical basis for preventing breast cancer metastasis.…”
Section: Tumor Metastasismentioning
confidence: 99%